The origins of the III Communist International - Carone, Edgard (FCL-UNESP Laboratório Editorial, 2008)
This texts analyses the rich historical process (from the end of the 19th century to the first two decades of the 20th century) of the class conflict and idealogy of the socialist movement, which will end up with the institution of the III Communist International.